(3GddZI hGddhf (B/s - (3YeQ, CMeO eNJGQs 1933-2003 ((3GdbGgQI (B:s (3YGde GdcJH fTQ(B-(3JhRjY(B-(3WHGYI ,s, 2009)
(3jJfGhd GdcJGH cKjQG ef bVGjG Gddhf ef LGfHjgG GddaXj hGddhfj hjQHW GdYde HGdaf, hjJNWi eG jSei HGdEfSGfjGJ hGdYdhe, djNQL cd gPG aj Yed eJcGed eJfGSb hjLeY GdcJGH CdaGX GdCdhGf GdYQHjI ef GdeYGLe GdbOjeI hGdMOjKI, hjbOe bGFeI HCge GdeaQOGJ hGdJYHjQGJ PGJ GdYdGbI HGdCdhGf hjYWj GgJeGeG NGUG HGSJNOGe CdaGX GdCdhGf aj GddZI GdEfLdjRjI(B.s
(3cTGaGJ (B: (3UaMI (B253-267.s
(3HHdjhLQGajI (B: (3UaMI (B345-252.s
Keywords: (3GddZI GdYQHjIs -- (3JYHjQGJ GUWdGMjIs; (3GddZI hGddhfs